Pharmacokinetics of an intravenous bolus dose of clonidine in children undergoing surgery. Issue 5 (2nd April 2020) - Nielsen, Bettina N.; Anderson, Brian J.; Falcon, Lars; Henneberg, Steen W.; Lauritsen, Torsten; Lomstein, Erik; Ydemann, Mogens; Afshari, Arash
Abstract: Background: Clonidine is used off‐label in children but only limited pediatric pharmacokinetic data are available for intravenously administered clonidine. Objectives: To determine pharmacokinetic parameter estimates of clonidine in healthy children undergoing surgery and to investigate age‐related differences. Furthermore, to investigate possible pharmacokinetic differences of clonidine between this group of children and a cohort with cardiac diseases. Methods: In a randomized placebo‐controlled trial (The PREVENT AGITATION trial), blood samples for clonidine pharmacokinetic analysis were collected in a proportion of the enrolled patients. Healthy children with ASA score 1‐2 in the age‐groups 1 to <2 years and 2‐5 years were randomized for blood sampling. Clonidine was administered as a single intravenous bolus of 3 µg/kg intraoperatively. Blood samples were drawn at baseline, 5, 10, 15, 30, 60 minutes after dosing and additionally every hour until discharge from the PACU. Clonidine analysis was performed on liquid chromatography‐mass spectrometry. Results: Data form eighteen children were available for pharmacokinetic analysis (ASA I; male/female: 17/1; age: 1‐5 years; weight 8.7‐24 kg). Population parameter estimates for the 2‐compartment model were similar to previous published data for children who underwent cardiac surgery. A pooled analysis including data from 59 children indicated clearance of 14.4 L h −1 70 kg −1 and volume of distribution of 192.6 L 70 kg −1 . No age‐related pharmacokinetic differences and no difference in time from administration of study medication to awakening were found. Children 1 to <2 years had a shorter PACU stay than children 2‐5 years (mean difference 17% 95% CI:3%‐34%, P = .02). Conclusion: Pharmacokinetic parameter estimates were similar for children undergoing general surgery and cardiac surgery given a single dose of intravenous clonidine. These results indicated that no dose reduction is needed in children aged 1 to <2 years compared with those 2‐5 years, which was supported by pharmacodynamic observations.